Profil Kecerdasan Jamak Mahasiswa Fakultas Ilmu Pendidikan Universitas Negeri Medan: Analisis Deskriptif Berbasis Multiple Intelligences - Nikita Fadhilah R. Lubis; Salsabila Salim Pardosi; Nadila Aulia Sastra; Dinda Marito Siregar; Dina Junita Sinaga; Tria Della Syahputri (Jurnal Pena Pendidikan Dasar, 2026)
This study aims to analyze the multiple intelligence profiles of students in the Faculty of Education, State University of Medan. Using a descriptive approach, this study explores the various types of intelligence possessed by students and their implications for the teaching and learning process. Data were collected through a questionnaire that had been tested for validity and reliability. The results indicate that students possess diverse intelligences, with interpersonal and linguistic intelligences being the most dominant. These findings are expected to provide insights for the development of a more responsive and inclusive curriculum.